Advanced Decision-Making Technique for Fire Suppression System Selection: A Case Study in the Plastic Manufacturing Industry - Ayyildiz, Ertugrul; Yildirim, Betul; Aydin, Nezir (WILEY, 2026)
Industrial facilities are environments with a high fire risk, where fires can rapidly escalate and cause significant damage if appropriate fire protection systems are not implemented. This study focuses on the critical task of selecting the most suitable fire suppression system for industrial facilities. To achieve this, we identify three main criteria-effectiveness, safety, and operational considerations-along with thirteen subcriteria to guide the selection process. The Spherical Fuzzy Analytic Hierarchic Process (SF-AHP) method is employed to determine the weights of these criteria through expert evaluations, followed by the Spherical Fuzzy Evaluation based on Distance from Average Solution (SF-EDAS) method to rank various fire suppression alternatives. A case study is conducted in a facility dedicated to producing plastic animal cages as a practical application of this methodology. This is a high-risk environment due to the explosive nature of the materials used. The results highlight Reaction Time as the most critical factor, followed by Impact on Operations, Flexibility, and Personnel Protection. In this case study, the clean agent system ranked highest, demonstrating its effectiveness in meeting the facility's specific needs. The proposed approach provides valuable insights for industrial plant managers aiming to enhance fire safety and protect personnel and assets in high-risk environments.
Keywords: fire safety; fire suppression systems; industrial facilities; multicriteria decision-making; spherical fuzzy sets; AVERAGE SOLUTION; FUZZY; Materials Science